2017
DOI: 10.2196/rehab.6319
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Mobile Health App for Patients With Dysphagia Following Head and Neck Cancer: A Qualitative Study

Abstract: BackgroundAdherence to swallowing rehabilitation exercises is important to develop and maintain functional improvement, yet more than half of head and neck cancer (HNC) patients report having difficulty adhering to prescribed regimens. Health apps with game elements have been used in other health domains to motivate and engage patients. Understanding the factors that impact adherence may allow for more effective gamified solutions.ObjectiveThe aim of our study was to (1) identify self-reported factors that inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…One barrier to adherence may be the total number of exercises required in the day (i.e. daily dose) [ 44 ]. Clinicians should recommend a prehabilitation program that balances the number of exercises required to create functional gains with one that patients can complete successfully.…”
Section: Discussionmentioning
confidence: 99%
“…One barrier to adherence may be the total number of exercises required in the day (i.e. daily dose) [ 44 ]. Clinicians should recommend a prehabilitation program that balances the number of exercises required to create functional gains with one that patients can complete successfully.…”
Section: Discussionmentioning
confidence: 99%
“…This may help enhance motor learning and improve engagement with therapy [46,47]. Biofeedback systems in cancer rehabilitation should be codesigned with users for specific clinical contexts to ensure that they are meaningful, accessible, and clinically effective [48,49]. Including appropriate elements of gamification (eg, points and levels) in the software development process may help promote engagement and adherence in some cohorts [50,51].…”
Section: Cancer Patient Carementioning
confidence: 99%
“…Two studies describe the development [63] and the verification [64] of apps aiming at reducing dysphagia after tumor therapy. In the 1 st article, important functions of an app for therapy of dysphagia were identified that were based on structured interviews with the affected individuals [63]. They contained biofeedback, a clear description of the pathologies, and instructions for exercises.…”
Section: Studies On Apps Regarding Swallowingmentioning
confidence: 99%